A cluster randomised controlled trial of a comprehensive accreditation intervention to reduce alcohol consumption at community sports clubs: study protocol. Issue 2 (30th September 2011) - Kingsland, Melanie; Wolfenden, Luke; Rowland, Bosco C; Tindall, Jennifer; Gillham, Karen E; McElduff, Patrick; Rogerson, John C; Wiggers, John H
Abstract : Introduction: Excessive alcohol consumption is responsible for considerable harm from chronic disease and injury. Within most developed countries, members of sporting clubs consume alcohol at levels above that of communities generally. Despite the potential benefits of interventions to address alcohol consumption in sporting clubs, there have been no randomised controlled trials to test the effectiveness of these interventions. The aim of this study is to examine the effectiveness of a comprehensive accreditation intervention with community football clubs (Rugby League, Rugby Union, soccer/association football and Australian Rules football) in reducing excessive alcohol consumption by club members. Methods and analysis: The study will be conducted in New South Wales, Australia, and employ a cluster randomised controlled trial design. Half of the football clubs recruited to the trial will be randomised to receive an intervention implemented over two and a half winter sporting seasons. The intervention is based on social ecology theory and is comprehensive in nature, containing multiple elements designed to decrease the supply of alcohol to intoxicated members, cease the provision of cheap and free alcohol, increase the availability and cost-attractiveness of non-alcoholic and low-alcoholic beverages, remove high alcohol drinks and cease drinking games. The intervention utilises a three-tiered accreditation framework designed to motivate intervention implementation. Football clubs in the control group will receive printed materials on topics unrelated to alcohol. Outcome data will be collected pre- and postintervention through cross-sectional telephone surveys of club members. The primary outcome measure will be alcohol consumption by club members at the club, assessed using a graduated frequency index and a seven day diary. Ethics and dissemination: The study was approved by The University of Newcastle Human Research Ethics Committee (reference: H-2008-0432). Study findings will be disseminated widely through peer-reviewed publications and conference presentations. Trial registration number: Australian New Zealand Clinical Trials Registry: ACTRN12609000224224.